Utilizing A Bioclimatic Architectural Approach on The Roof To Optimize Building Thermal Performance. Case Study: Universitas Diponegoro Campus Mosque - Syarifiyah, Kharizma Aulia; Widiastuti, Ratih; Pramesti, Previari Umi (Jurnal Arsitektur dan Perencanaan (JUARA), 2024)
Local wisdom enhances building aesthetics and imparts philosophical values. Bioclimatic architecture has become popular among architects and designers because it reduces energy consumption without harming the environment. A study at the Universitas Diponegoro Campus Mosque applied bioclimatic design using a traditional joglo roof model simulated with Autodesk Ecotect. Measurements showed the maximum suhue on the second floor reached 28°C. Simulations indicated that bioclimatic design could reduce indoor suhues by 4.3°C - 5.2°C to 24.5°C. This result shows a lower suhue difference compared to the existing design by 7.5°C. This design can be a prospective solution for improving thermal comfort and providing an environmentally friendly design.